The method for identifying emergency section considering the model of nonstationary modes of the gas-transport system - Тевяшев, Андрей Дмитриевич; Гусарова, Ирина Григорьевна; Каминская, Анна Владимировна (Eastern-European Journal of Enterprise Technologies, 2012)
It is proposed a method for identifying emergency situations when gas leaks appears on the pipeline segments, based on the mathematical modeling of nonstationary nonisothermal modes of the multi-threads linear sections of the gas-transport system